The single-cell transcriptional landscape of lung cells from PCV2d-infected mice - Chen, Yunlong; Fan, Gang; Yang, Bin; Fan, Xinyi; Chen, Haiyan; Ma, Zhuoyuan; Lou, Jiao; Xu, Jingmei; Wang, Yan; Zhang, Shiqiang (Frontiers in Microbiology, 2025)
IntroductionPorcine Circovirus (PCV2) infection is prevalent in pig farming and causes significant economic losses. In recent years, the PCV2d subtype has become the most prevalent genotype worldwide, exhibiting higher virulence, leading to more severe viremia and organ damage. Therefore, studying the biological characteristics of the PCV2d subtype is of great significance.MethodsWe established a PCV2d infection model using BALB/c mice and employed single-cell RNA sequencing (scRNA-seq) to systematically analyze the transcriptome of 10 cell types in the lung tissues of infected mice. We developed a comprehensive marker gene catalog for these cell types.ResultsCompared to uninfected mice, PCV2d infection induced extensive viral replication and immunosuppressive responses in most cell types. Monocyte macrophages with high levels of viral replication, pro-inflammatory cytokines, and various cell population interactions occurring through CD40-CD40L and CXCL14-CXCR4 were identified. These cells predominantly mediate antigen presentation and processing pathways in vivo, contributing to PCV2d-driven inflammatory lung injury.DiscussionOur data uncovered a complex unique immune response scenario in the lung tissue of mice after PCV2d infection, deciphering the potential mechanisms underlying PCV2d-driven inflammatory responses in mice. Furthermore, this study provides a rich database for the molecular basis of different cell types' responses to PCV2d infection.